Streamlining Design Verification and Protocol Validation - Jaiswal, Hritik (Thapar Institute of Engineering and Technology, 2025)
Design verification is a critical phase in the development of Intellectual Property (IP) cores to ensure they function correctly and meet the intended specifications. As IP cores are increasingly reused across multiple systems, the need for a robust and efficient verification process has become more crucial. This paper explores various methodologies and tools used for IP verification, including simulation-based techniques, formal verification, and hardware-assisted approaches like FPGA prototyping. We highlight the importance of creating a comprehensive testbench, using coverage metrics, and adopting universal verification methodologies (UVM) to improve verification efficiency and quality. The challenges posed by the growing complexity of IP cores and the need for scalability in verification are also discussed. The ultimate goal is to achieve a bugfree design before integration into larger systems, reducing timeto-market and ensuring reliable performance in end products. By addressing the evolving challenges of IP verification, this paper provides insights into best practices and emerging trends in the field, supporting more efficient design cycles and higher quality IP cores.
Keywords: UVM; APB; ASIC; IP; FSM; AXI; AHB; TX; RX